2000
DOI: 10.7326/0003-4819-133-5-200009050-00007
|View full text |Cite
|
Sign up to set email alerts
|

Joint Injury in Young Adults and Risk for Subsequent Knee and Hip Osteoarthritis

Abstract: Young adults with knee injuries are at considerably increased risk for osteoarthritis later in life and should be targeted in the primary prevention of osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
461
2
23

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 653 publications
(510 citation statements)
references
References 27 publications
15
461
2
23
Order By: Relevance
“…Alone, SHU9119 caused a modest inhibition of IL-1 but had no effect on TNF--induced IL-6 or IL-8 production, consistent with its dual agonist/antagonist nature. Remarkably, while SHU9119 was unable to block the effect of -MSH, it abridged the anti-inflammatory activity of D[TRP] 8 --MSH, thus suggesting a potential role for MC 3 in chondroprotection, which agrees with previous studies reporting MC 3 agonist activity of this peptide [51,76,79]. Moreover, at higher concentrations of -MSH, the presence of SHU9119 synergistically reduced IL-6 release, thereby signifying that SHU9119 may be concerting efforts with -MSH via either activation of MC 1 and/or MC 5 .…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Alone, SHU9119 caused a modest inhibition of IL-1 but had no effect on TNF--induced IL-6 or IL-8 production, consistent with its dual agonist/antagonist nature. Remarkably, while SHU9119 was unable to block the effect of -MSH, it abridged the anti-inflammatory activity of D[TRP] 8 --MSH, thus suggesting a potential role for MC 3 in chondroprotection, which agrees with previous studies reporting MC 3 agonist activity of this peptide [51,76,79]. Moreover, at higher concentrations of -MSH, the presence of SHU9119 synergistically reduced IL-6 release, thereby signifying that SHU9119 may be concerting efforts with -MSH via either activation of MC 1 and/or MC 5 .…”
supporting
confidence: 91%
“…However, in spite of the potential of melanocortin peptides to limit inflammation, few studies have looked at their chondroprotective properties. We have recently demonstrated that both the melanocortin receptor pan-agonist -MSH and [DTRP 8 ]--MSH (structures shown in Table 1), which shows selectivity for MC 3 , ameliorate TNF--induced chondrocyte apoptosis and the release of pro-inflammatory cytokines and MMP's [64]. Now, we describe the ability of the of melanocortins to: 1) prompt a homeostatic control over impact-induced inflammatory cytokine production, 2) confine chondrocyte death and cartilage damage to injury site, whilst…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent estimates suggest that posttraumatic arthritis is responsible for 12% of the 21 million cases of OA in the US, at a cost of ϳ$7 billion annually to the US economy (2). Posttraumatic arthritis also causes disability in young and middle-aged patients, unlike idiopathic OA (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Acute traumatic joint injury in young adults leads to an increased risk of developing osteoarthritis (OA) later in life (1)(2)(3), despite efforts to intervene in this process by surgically stabilizing injured joints (4). Although the mechanism by which injury leads to tissue degeneration remains to be elucidated, several injuryrelated factors may contribute to the development of OA.…”
mentioning
confidence: 99%